Picture Book erancangan Buku Bergambar sebagai Media Edukasi Sopan Santun Anak - Lemong, Juliana Laurensia; Yuwono, Elisabeth Christine; Yusuf, Vanessa (Serat Rupa: Journal of Design, 2023)
Manner are an important aspect of social life. But along with the times, there have been several cultural shifts, one of which is the manner culture. Children are often not aware of how to be polite in everyday life. Because of this problem, manners need to be re-taught to children from an early age. One of the media that can be used is through picture books. This media was chosen because picture books are media that are close to and are still liked by children. In addition, children are also more interested in seeing more pictures than writing. The aim of the design is to design a picture book by applying Edgar Dale's learning pyramid, namely learning that is practiced so that it becomes a new habit. The method used to conduct this research is a qualitative descriptive method through literature studies. The unique idea raised in the design of this picture book is an interactive feature in the form of a courtesy activity sheet. This feature can be accessed via a code on the online journal file. In addition to children learning about manners through stories, children can also practice it in everyday life and then remember again by filling out activity sheets through the media of this picture book.